Support for a European metrology network on food safety Food-MetNet. (December 2021) - Ogrinc, Nives; Rossi, Andrea Mario; Durbiano, Francesca; Becker, Roland; Milavec, Mojca; Bogožalec Košir, Alexandra; Kakoulides, Elias; Ozer, Hayrettin; Akçadag, Fatma; Goenaga-Infante, Heidi; Quaglia, Milena; Mallia, Silvia; et al.
Abstract: This paper describes Food-MetNet, a coordinated preparatory initiative to establish the European Metrology Network on Food Safety (EMN-FS). Food-MetNet aims to establish a long-term ongoing dialogue between the metrology community and relevant stakeholders, in particular, European Union Reference Laboratories (EURLs), National Reference Laboratories (NRLs) and the Joint Research Centre (JRC). This dialogue is meant to support the collection of needs from stakeholders, the take-up of metrological research output and the development of the roadmaps needed to navigate future research.